Author Response: Excess Mortality And Hospitalized Morbidity In Newly Treated Epilepsy Patients. (31st January 2017) - Kwan, Patrick; Chen, Zhibin; Liew, Danny
Abstract : We thank Dr. Sethi for the comment on our article. 1 We acknowledge that the association between epilepsy and other conditions may be due to confounders, but the association is present nonetheless; this demonstrates that the larger burden conferred by epilepsy is attributable in part to comorbid conditions. There may even be a triangular relationship among epilepsy, psychiatric, and physical comorbidities, operating through unhealthy lifestyles in terms of diet and physical activity. There was no capacity in our study to reliably assess and account for such lifestyle factors long term. However, this is a worthwhile area for future research, made feasible by the ubiquitous wearable devices capable of tracking physical activity. 2